Validity of a portable force platform for assessing biomechanical parameters in three different tasks - Peterson Silveira, R.; Stergiou, P.; Carpes, F. P.; de S. Castro, F. A.; Katz, L.; Stefanyshyn, D. J. (Sports Biomechanics, 2017)
The aim of this study was to determine the precision and accuracy of the vertical and anterior-posterior force components of the portable PASCO PS-2142 force plate. Impulse, peak force, and time to peak force were assessed and compared to a gold standard force plate in three different tasks: vertical jump, forward jump, and sprint start. Two healthy male participants performed ten trials for each task, resulting in 60 trials. Data analyses revealed good precision and accuracy for the vertical component of the portable force plate, with relative bias and root mean square (RMS) error values nearly the same in all tasks for the impulse, time to peak force, and peak force parameters. Precision and accuracy of the anterior-posterior component were lower for the impulse and time to peak force, with relative bias and RMS error values nearly the same between tasks. Despite the lower precision and accuracy of the anterior-posterior component of the portable force plate, these errors were systematic, reflecting a good repeatability of the measure. In addition, all variables presented good agreement between the portable and gold standard platforms. Our results provide a good perspective for using the aforementioned portable force plate in sports and clinical biomechanics. ABSTRACT FROM AUTHOR